Learning democracy digitally? The internet and knowledge of democracy in nondemocracies. Issue 8 (16th November 2020) - Placek, Matthew
ABSTRACT: The study of public opinion in nondemocratic states has found that people often say they support democracy, yet they show little demand for democratization or regime change. Given this paradox, recent scholarship has shown that these attitudes exist because people who live under the rule of non-democratic regimes often misunderstand what democracy is. Individuals in these societies often think that authoritarian ways of governance are fundamental aspects of democracy. In another strain of literature, research has shown that the internet can alter demands for democracy and increase protest activity in non-democracies. Given these findings, this study investigates what impact the internet has on understanding democracy in non-democracies. Using World Values Survey data and employing two different styles of empirical modelling, the study finds that consuming information from the internet leads to a better understanding of essential elements of democracy. The findings also show that the effects are more pronounced in autocracies than they are in illiberal regimes.